Value Added Service and Service Quality from the Customer’s Perspective: An Empirical Investigation in Thai Telecommunication Industry - Srikanjanarak, Saowanee; Omar, Azizah; Ramayah, T (UI Scholars Hub, 2021)
Increasing global competition has led to an intensively competitive market among service providers. Several organizations have created and developed a variety of products or services; in particular the telecommunications industry has developed mobile phone services. Various value-added services linked to mobile phone services, such as communication, entertainment, information services and money transfer services have been intensively incorporated to sustain and serve the customer’s need, which in turn demands performance maximization. In service marketing literature, SERVQUAL and SERVPERF have been reported as failing to measure service quality in new industries such as the retail industry’s B2B service. Therefore, service quality models for the mobile phone service industry need to be further developed.Service quality models have placed little focus on value-added services and no research has yet operationalized the concept of value-added services in a service quality model from the customer’s perspective of the service industry. Hence, this paper aims to conceptualize a service quality model based on Gronroos’ Model, other exploratory research and the current market situation in the service context. A total of 998 structured questionnaires were distributed to pre-paid mobile phones users in nine provinces around Thailand. The results indicate four dimensions of service quality. The value-added services have shown a particularly high level of measurements of satisfaction. These findings reveal a meaningful insight into how customers perceive the value-added services offered by service providers. This will help managers to design an appropriate variety of service options that suit their customers and in turn may lead to the development of a long-term relationship with their organizations